Metabolism of Stilbenoids by Human Faecal Microbiota - Jarosova, Veronika; Veselý, Ondřej; Marsik, Petr; Jaimes, Jose Diogenes; Smejkal, Karel; Kloucek, Pavel; Havlik, Jaroslav (Molecules, 2019)
Stilbenoids are dietary phenolics with notable biological effects on humans. Epidemiological, clinical, and nutritional studies from recent years have confirmed the significant biological effects of stilbenoids, such as oxidative stress protection and the prevention of degenerative diseases, including cancer, cardiovascular diseases, and neurodegenerative diseases. Stilbenoids are intensively metabolically transformed by colon microbiota, and their corresponding metabolites might show different or stronger biological activity than their parent molecules. The aim of the present study was to determine the metabolism of six stilbenoids (resveratrol, oxyresveratrol, piceatannol, thunalbene, batatasin III, and pinostilbene), mediated by colon microbiota. Stilbenoids were fermented in an in vitro faecal fermentation system using fresh faeces from five different donors as an inoculum. The samples of metabolized stilbenoids were collected at 0, 2, 4, 8, 24, and 48 h. Significant differences in the microbial transformation among stilbene derivatives were observed by liquid chromatography mass spectrometry (LC/MS). Four stilbenoids (resveratrol, oxyresveratrol, piceatannol and thunalbene) were metabolically transformed by double bond reduction, dihydroxylation, and demethylation, while batatasin III and pinostilbene were stable under conditions simulating the colon environment. Strong inter-individual differences in speed, intensity, and pathways of metabolism were observed among the faecal samples obtained from the donors.
Keywords: kolon; feces; Feces; Resveratrol; Tandem Mass Spectrometry; fenoly; Phenols; Colon; stilbeny; lidé; Microbiota; Stilbenes; Chromatography, Liquid; fermentace; hmotnostní spektrometrie; resveratrol; mikrobiota; tandemová hmotnostní spektrometrie; Fermentation; Mass Spectrometry; chromatografie kapalinová; Humans